Research on male regular clergy in modern Spain and some development perspectives (Estudios de Historia de España, 2020)
This paper provides a brief overview of Spanish modernist historiography, dedicated to the regular clergy, along with the development of some current issues that occupy historians in this field. In addition, it proposes some issues that await further study or that require further development. Overall, we want to draw the attention of the scientific community to a field of research that deserves greater attention given the centrality and weight of the male regular clergy in the Spanish society of the Ancien Régime and the availability of a considerable documentary mass that would facilitate their study.
Keywords: Regular Clergy; Historiography; Modern Age; Spain; Archives